(untitled) (International Journal of Engineering and Computer Science, 2018)
This paper aims at presenting a novel technique to find duplicate records in hierarchical (XML) data which contains multimedia attributes. Now a days the data is being stored in more complex and semistructured or hierarchical structure and the problem arose is how to detect duplicates on this XML data. Due to differences between various data models we cannot apply same algorithms which are for single relation on XML data. The objective of this paper is to detect duplicates in hierarchical data which contain textual and multimedia data like images, audio and video. Also to act according to user choice on that data like delete, update etc. Also to prune the duplicate data by using pruning algorithm that is included in proposed system. Here Bayesian network will be used for duplicate detection, and by experimenting on both artificial and real world datasets the MULTIDUP method will be able to perform duplicate detection with high efficiency and effectiveness. This method will compare each level of XML tree from root to the leaves. The first step is to go through the structure of tree comparing each descendant of both datasets inputted and find duplicates despite difference in data.